1233 A QUALITY IMPROVEMENT PROJECT TO IMPROVE THE MONITORING OF FLUID INTAKE ON OLDER PERSONS' WARDS. (16th January 2023) - James, E; Devine, O P; Ali, W; Butler, S; Fleet, J
Abstract: Introduction: Dehydration is the most common fluid and electrolyte imbalance in older adults; hospitalised older adults with markers of dehydration have mortality rates of 45% (Hodgkinson B et al, 2003). The current method of measuring fluid intake on wards is to record this hourly on fluid balance charts however this is often poorly documented (Jeyapala S et al, 2015). We wished to improve the accuracy of recording the oral fluid intake of older adults by introducing a simplified bedside chart which could identify those at risk of dehydration. Methods: Using PDSA methodology, a team of doctors directly observed and recorded the oral fluid intake of patients in a 6-bed bay on an older persons' ward for 8 continuous hours. The collected data was compared to that recorded on pre-existing fluid balance charts. A new bedside fluid intake chart was then introduced; this laminated chart included example volumes of common drink receptacles and used 'ticks' to record each time fluid was consumed. A repeat PDSA cycle was performed with a second observation day. Guided interview qualitative methodology was used to obtain feedback from nursing staff. Results: The mean difference in observed fluid intake versus charted fluid intake prior to intervention was 287.50ml (SD = 152.27, n = 6) and 95ml post intervention (SD = 94.21, n = 5). Analysis with an unpaired two sample t-test demonstrated a significant difference (p = 0.03). Qualitative feedback from nursing staff reported it to be easier to use and more likely to be correctly completed. Conclusion: The redesigned fluid intake chart led to statistically significant improvements in the accuracy of recording fluid intake. A further PDSA cycle across a whole ward will inform feasibility on a larger scale of early identification of dehydration. The tool may also allow assessment of the effectiveness of hydration aids.